Implementing social networking features in a web environment - Mohit Khandelwal. (2013)
This report has been written with the aim of providing the reader with a vivid summary of the author’s work and learning experience during completion of the Final Year Project at School of Computer Engineering at Nanyang Technological University, Singapore. For the purpose of this project, a website built by a PhD student- Knowledge Web for Memetic Computing- was enhanced to include social networking features and connect memetic scientists.